Population structure and risk assessment of invasive species Asystasia gangetica in urban area of Bandung, West Java, Indonesia - DIAN ROSLEINE; ANGGI RIQQA KHALISHAH (Society for Indonesian Biodiversity, 2024)
Abstract. Rosleine D, Khalishah AR. 2024. Population structure and risk assessment of invasive species Asystasia gangetica in urban area of Bandung, West Java, Indonesia. Biodiversitas 25: 2374-2381. Asystasia gangetica (L.) T. Anderson is a weed from Africa that has a high adaptation to wide ecological conditions. This research aims to assess the population structure of A. gangetica in Bandung City, West Java, Indonesia and to conduct risk assessment to determine management decisions. This research was conducted from January to February 2023 by establishing a total of 106 plots with size of 1 m2 to measure the population structure at adult and juvenile stages, and number of fruits. Plot sized 0.4 m2 was used to count the seed in a 10 cm soil depth. A risk assessment was conducted, which consisted of 12 questions of risk analysis (invasiveness, impact, and potential distribution) and 20 questions of management feasibility (control cost, distribution, and persistence). The results of principal component analysis and clustering analysis show three groups based on population structure (PC1 49.12% and PC2 28.44%). The first cluster consists of three sub-districts and shows a set of early colonized populations indicated by low juvenile stage, while the second cluster (14 sub-districts) and third cluster (13 sub-districts) show more established population yet still recently colonized, which is indicated with medium-high juvenile and reproductive (fruit) stage. The risk assessment results in 91.2 of the risk analysis score (medium) and 169.7 of the management feasibility score (negligible), implying the need to manage the site. Nevertheless, its wide-range of habitat tolerant and population characteristics potentially threaten biodiversity and harm the agricultural sector at once. Therefore, early countermeasure is needed as an effort to minimize greater risks in the future.